Digital Transformation in the Maritime Supply Chain: Systematic Literature Review: Transformasi Digital Rantai Pasokan Maritim: Literature Review - Maya Revanola Zainida; Rofiqoh Nur Rohmah; Fisilmi Azizah Rahman (LPPM Telkom University Surabaya, 2026)
The maritime sector plays a vital role in global trade and increasingly requires digital transformation to address operational complexity, logistics disruptions, and supply chain resilience challenges. This study aims to analyze digital transformation technologies in maritime supply chains through a Systematic Literature Review (SLR). The review followed the PRISMA protocol, including identification, screening, eligibility, and inclusion stages. Literature searches were conducted using Scopus, ScienceDirect, and Google Scholar with keywords related to digital transformation, maritime supply chains, smart ports, blockchain, and IoT. From 35 identified articles, 20 peer-reviewed studies published between 2020 and 2026 were selected after screening and full-text evaluation. The findings indicate that technologies such as IoT, AI, Blockchain, Big Data, ERP systems, and smart port technologies improve operational efficiency, transparency, real-time monitoring, and supply chain resilience. However, successful implementation depends on infrastructure readiness, cybersecurity, policy support, interoperability, and human resource capabilities.